Upaya Peningkatan Pendapatan Rumah Tangga Melalui Pengembangan Usaha Pada Kelompok Pengrajin Batik Tulis Kampoeng Batik Desa Karaskepoh Kabupaten Rembang - Riskin Hidayat; Siti Alliyah (Journal of Dedicators Community, 2017)
AbstractThe program IbM is implemented in the Karaskepoh village, Pancur district, Rembang with partners Craftsmen Group Batik Sekar Melati and Sekar Jagad. Karaskepoh village is one of the tourist village kampoeng batik in Rembang because many of its citizens who work as batik, so local knowledge is necessary to get attention in IbM program. IbM purpose of this is to increase revenue Craftsmen Group Batik Sekar Melati and Sekar Jagad. The methodology carried out is counseling, training of Management and Entrepreneurship, and business assistance. IbM program results include: 1) There is an increasing role of group members batik and business networking; 2) Batik products Sekar Melati and Sekar Jagat group has had a more diverse media promotion, both conventional ones such as brochures, business cards, and banners although online media promotions is using a blog; 3) Batik products Sekar Melati and Sekar Jagad group has had packaging and labels a good and interesting; 4) Group batik Sekar Melati and Sekar Jagat has had a good product catalog; 5) It has been structured proposal batik feasibility Sekar Melati and Jagad Sekar group; and 6) The group batik Sekar Melati and Sekar Jagat has had an orderly and good bookkeeping.